2014
DOI: 10.1007/s00253-014-5602-1
|View full text |Cite
|
Sign up to set email alerts
|

A freshwater bacterial strain, Shewanella sp. Lzh-2, isolated from Lake Taihu and its two algicidal active substances, hexahydropyrrolo[1,2-a]pyrazine-1,4-dione and 2, 3-indolinedione

Abstract: Cyanobacterial blooms have become a serious problem in Lake Taihu during the last 20 years, and Microcystis aeruginosa and Synechococcus sp. are the two dominant species in cyanobacterial blooms of Lake Taihu. A freshwater bacterial strain, Shewanella sp. Lzh-2, with strong algicidal properties against harmful cyanobacteria was isolated from Lake Taihu. Two substances with algicidal activity secreted extracellularly by Shewanella sp. Lzh-2, S-2A and S-2B, were purified from the bacterial culture of strain Lzh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…It is interesting to find that some algicidal bacteria such as Cytophaga strains J18/M01 (Mirsutani et al 1992) and A5Y (Imai et al 1993), Flavobacterium strain 5N-3 (Imai et al 1992), and Flavobacteriaceae strain S03 (Roth et al 2007) must reach a cell density of at least 10 6 cells mL −1 before they show any algicidal activity. Li et al (2014) found that Shewanella sp. Lzh-2 must reach a bacterial cell density threshold of at least 10 8 cells mL −1 before any algicidal compound can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to find that some algicidal bacteria such as Cytophaga strains J18/M01 (Mirsutani et al 1992) and A5Y (Imai et al 1993), Flavobacterium strain 5N-3 (Imai et al 1992), and Flavobacteriaceae strain S03 (Roth et al 2007) must reach a cell density of at least 10 6 cells mL −1 before they show any algicidal activity. Li et al (2014) found that Shewanella sp. Lzh-2 must reach a bacterial cell density threshold of at least 10 8 cells mL −1 before any algicidal compound can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Lzh‐2, showed algicidal activity. Cyclo(Gly‐Phe) belongs to the diketopiperazine family, which contains a large group of small molecules produced by a wide range of microbes that exhibit many valuable biological properties (Ortiz‐Castro et al ., ), including antibacterial (Fdhila et al ., ), algicidal (Li et al ., ; Guo et al ., ; Li et al ., ; Lin et al ., ) and signal (sexual pheromone) (Gillard et al ., ) activities. During the sexual reproduction of the diatom Seminavis robusta , diproline (proline‐derived diketopiperazine) acting as the sexual pheromone of the attracting mating type (MT − cells) can induce the migratory behavior of the migrating mating type (MT + cells) (Gillard et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . () found that another indole derivative, isatin, which is produced by Shewanella sp. Lzh‐2, showed algicidal activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations